ANALISIS KETERAMPILAN MENULIS PUISI SISWA DITINJAU DARI MOTIVASI BELAJAR SISWA - Aulianda Kitty Pratiwi; Rien Anitra; Mertika Mertika (JS (JURNAL SEKOLAH), 2023)
Abstract : Analysis of Students' Poetry Writing Skills in terms of Student Learning Motivation in Class IV SD Negeri 58 Singkawang Selatan. This study aims to 1) analyze students' poetry writing skills in terms of high student learning motivation in class IV SD Negeri 58 Singkawang Selatan 2) analyze students' poetry writing skills in terms of students' learning motivation in class IV SD Negeri 58 Singkawang Selatan 3) analyze skills writing poetry students in terms of low learning motivation in class IV SD Negeri 58 Singkawang Selatan. This type of research is descriptive qualitative. The data collection technique used was a poetry writing test and a learning motivation questionnaire. The technique used in this study is by using 1) data collection techniques 2) measurement techniques 3) direct communication techniques 4) documentation techniques. The subjects in this class were fourth graders at SD Negeri 58 Singkawang Selatan, totaling 29 people. The results of this study indicate that 1) students who have high poetry writing skills have moderate learning motivation, 2) students who have moderate poetry writing skills have sufficient motivation to learn 3) students who have less poetry writing skills have less motivation to learn. This is because students are still less skilled in choosing and arranging words in the form of poetry, there is an assumption that poetry is difficult for students. The results of poetry writing skills can be seen from the results of students' poetry writing tests in the less category.Keywords : Poetry Writing Skills, Learning Motivation, Elementary School Abstrak : Analisis Keterampilan Menulis Puisi Siswa ditinjau dari Motivasi Belajar Siswa di Kelas IV SD Negeri 58 Singkawang Selatan. Penelitian ini  bertujuan untuk 1) menganalisis keterampilan menulis puisi siswa ditinjau dari motivasi belajar siswa tinggi di kelas IV SD Negeri 58 Singkawang Selatan 2) menganalisis keterampilan menulis puisi siswa ditinjau dari motivasi belajar siswa sedang di kelas IV SD Negeri 58 Singkawang Selatan  3) menganalisis keterampilan menulis puisi siswa ditinjau dari motivasi belajar rendah di kelas IV SD Negeri 58 Singkawang Selatan. Jenis penelitian ini adalah kualitatif deskriptif. Teknik pengumpulan data yang digunakan adalah tes menulis puisi dan angket motivasi belajar. Teknik yang digunakan dalam penelitian ini yaitu dengan menggunakan 1) teknik pengumpulan data 2) teknik pengukuran 3) teknik komunikasi langsung 4) teknik dokumentasi. Subjek dalam ini siswa kelas IV SD Negeri 58 Singkawang Selatan yang berjumlah 29 orang. Hasil penelitian ini menunjukan bahwa 1) siswa yang memiliki keterampilan menulis puisi tinggi memiliki motivasi belajar yang sedang, 2) siswa yang memiliki keterampilan menulis puisi sedang memiliki motivasi belajar cukup 3) siswa yang memiliki keterampilan menulis puisi kurang memiliki motivasi belajar yang kurang. Hal ini dikarenakan siswa masih kurang terampil dalam memilih dan menyusun kata-kata dalam bentuk puisi, adanya anggapan bahwa puisi merupakan hal yang sulit bagi siswa. Hasil dari keterampilan menulis puisi dapat dilihat dari hasil tes menulis puisi siswa dengan kategori kurang.Kata Kunci : Keterampilan Menulis Puisi, Motivasi Belajar, Sekolah Dasar